Spin-Correlated Top Quark Decays in ttW Production - Wang,Tingjie (2025)
This thesis investigates the modeling of top quark pair production in association with a W boson, focusing in particular on off-shell effects and spin correlations within the framework of the Narrow Width Approximation (NWA). Full NLO QCD computations for the complete ttW process, including finite-width and spin-correlation effects, offer the highest theoretical accuracy. However, they are computationally intensive, which limits their practical applicability and hinders extensions to higher-order simulations such as NNLO. As a more efficient approach, we validate the feasibility of the NWA by analyzing its theoretical foundations and comparing leading-order (LO) simulations—including double-, single-, and non-resonant contributions—with full off-shell results. Through detailed cross-section and differential distribution studies, we confirm that the NWA introduces an acceptably small error. To improve the modeling of spin correlations beyond conventional leading-order decay methods, we propose a new methodology by modifying matrix element generation within the MadGraph5_aMC@NLO framework. This allows us to fully preserve the spin correlations between the top quarks at LO under the NWA. Our method successfully reproduces spin-correlation observables at the matrix-element level, showing improved agreement with theoretical expectations compared to standard LO decay treatments such as MadSpin. These results highlight the advantages of incorporating spin-correlated decays directly into the matrix-element generation, offering a robust and computationally efficient approach for precision simulations involving heavy particle decays.
Keywords: Top quark; Spin correlation; Narrow Width Approximation (NWA); Off-shell effects; ttW production; MadGraph5_aMC@NLO; Matrix element; Madspin